EFEKTIVITAS PENGGUNAAN WORDWALL DALAM PEMBELAJARAN DARING PADA MATERI PERDAGANGAN ANTAR DAERAH DAN PERDAGANGAN INTERNASIONAL - Fikriyah, Na’imatul; Fihronniyah, Ira Wirdatul; Ratnawati, Etty (JSPH : Jurnal Sosial Politik Humaniora, 2024)
Wordwall is a medium that makes student more interested in the learning process, so that they are actively involved in the learning process and understand the material presented. So that it can improve students' skills and understanding. Based on this research and previous research, it can be understood that the Wordwall learning media is not only used for language, history and mathematics subjects but can also be used in social studies subjects. Wordwalls can also be used in distance learning because teachers can share activities they create with students online. Additionally, Wordwall offers a variety of tools and features to analyze students' progress in understanding course material. Therefore, Wordwall is a useful tool in education that aims to create a more interactive and interesting learning experience by using specific words and concepts. Keywords: Wordwall, online learning, student interactivity